Research Participation as Work: Comparing the Perspectives of Researchers and Economically Marginalized Populations - Davidson, Peter; Page, Kimberly (American journal of public health (1971), 2012)
We examined the historical and regulatory framework of research with human participants in the United States, and described some possible unintended consequences of this framework in the context of paying young injection drug users for their time participating in behavioral and medical research. We drew upon our own experiences while conducting a long-running epidemiological study of hepatitis C virus infection. We found that existing ethical and regulatory framings of research participation may lead to injustices from the perspectives of research participants. We propose considering research participation as a specialized form of work and the use of community advisory boards to facilitate discussion about appropriate compensation for research participation among economically marginalized populations.